2021
DOI: 10.24874/ti.931.07.20.11
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Mechanical Analysis and Optimization of Hybrid Carbon-Epoxy Composites Wear using Taguchi Method

Abstract: The purpose of this research work is to explore the potential of nano silicon dioxide (nSiO2) with the carbon fiber reinforced epoxy (CF/Ep) composite for achieving better wear resistance and viscoelasticity. An effort is made to improve the material behavior by modifying epoxy with silane treated nSiO2. Ultrasonication process is used to disperse the nano particles uniformly within the matrix material. Mono CF/Ep composite and hybrid nSiO2-CF/Ep composites are fabricated by vacuum bagging method. Post curing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…A confirmation test validates analysis findings (Shonda and Jeffrey, 2013; Divya et al ., 2021). The predictive equation can be used to determine the anticipated S/N ratio of SWR at the optimal control variable level (Sudheer et al ., 2012; Ravikantha et al.…”
Section: Resultssupporting
confidence: 76%
“…A confirmation test validates analysis findings (Shonda and Jeffrey, 2013; Divya et al ., 2021). The predictive equation can be used to determine the anticipated S/N ratio of SWR at the optimal control variable level (Sudheer et al ., 2012; Ravikantha et al.…”
Section: Resultssupporting
confidence: 76%
“…The KS value obtained experimentally for CF-PLA composite at optimised condition was lower in comparison to PLA composite. KS value of PLA composite was reduced due to higher load bearing capacity along with increased strength and stiffness by reinforcement of carbon fibers, the obtained results are in line with the previous literature works [12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Effect Of Carbon Fiber On Density Of Pla Compositesupporting
confidence: 90%
“…The difference between experimental and theoretical densities indicate presence of voids and pores in the fabricated composite samples, that have a considerable impact on the material properties [17]. The CF-PLA The statistical approach of Analysis of variance (ANOVA) was used to generate a set of conclusions according to the experimental results and significant contributions of each factor on the response [21]. ANOVA was performed for 5% level of significance and 95% degree of confidence.…”
Section: Effect Of Carbon Fiber On Density Of Pla Compositementioning
confidence: 99%
“…The hybrid composites are used for many application and replacing wood, wood fiber composites, and conventional materials. [33] Divya et al [34] carried out experimental work on nano silicon dioxide with carbon fiber reinforced epoxy composite for getting better wear resistance and visco-elasticity through Taguchi technique and ANOVA. The result revealed that lowest specific wear rate and coefficient of friction are in 3 wt% nSiO 2 filled CF/Ep hybrid composite.…”
Section: Effect Of Solid Lubricants On Friction and Wearmentioning
confidence: 99%